Frequency of Hepatitis C and Hepatitis B Virus in Rural Areas of Pakistan, An Experience at Tertiary Care Hospital in Khurrianwala (Medical Forum Monthly, 2024)
Objective: To find out the frequency of Hepatitis C virus and Hepatitis B virus in Rural areas of Pakistan, an experience at a Tertiary Care Hospital in Khurrianwala.Study design: Cross-sectional / comparative study. Place and Duration of study: This study was conducted at the Department of Pathology, Abwa Hospital and Research Centre, Khurrianwala, Faisalabad from 01.01.2019 to 31.03.2019.Materials and Methods: The study included a total of 1000 patients visiting the screening camp. The screening camp was arranged to screen the individuals for viral hepatitis B and C in the hospital premises. General public, especially of the surrounding villages, were informed about the location and timings of the camp.All healthy, asymptomatic adults not previously screened were included. Individuals previously tested and confirmed of disease, or on treatment for HBV/HCV, were excluded from the study.Results: In this study, a total of 1000 patients were screened, each for hepatitis B and C virus. All these patients belonged to rural areas of khurrianwala. Among these patients 489 (48.9%) were HCV positive and 511 were (51.1%) found to be HCV negative, whereas 47 (4.7%) were HBV positive and 953 (95.3%) were found to be HBV negative.Conclusion: In developing countries like Pakistan, with high rates of HCV and HBV infection rates, screening is mandatory for early diagnosis and ICT is easy, practical, economical and convenient. However, patients should be guided to get ELISA done to avoid false positive results.